A Review on High Entropy Alloys Coatings: Fabrication Processes and Property Assessment. Issue 8 (11th June 2019) - Li, Junchen; Huang, Yongxian; Meng, Xiangchen; Xie, Yuming
Abstract : Surface coatings can enhance the mechanical and functional properties of substrates and keep good balance between specific mechanical properties and sufficient surface performance of the components. Coatings composed of high entropy alloys (HEAs) and HEA‐based materials, including metallic, ceramics, and composites have attracted the global attention and developed rapidly over the last decade, owing to their outstanding properties. Here, the authors provide a critical review of the state‐of‐the‐art for HEA‐based coatings, aiming to address the related conceptions, designing principles, microstructural, and mechanical evolutions during fabrication and post‐treatments process. The surface properties which are not limited to anti‐corrosion, anti‐radiation, and anti‐diffusion and their underlying mechanisms are analyzed. The development tendency and future applications are classified and discussed, including the basic researches about HEAs, the regulations of fabrication techniques and the exploring of functional properties of HEA‐based coatings. Due to their superior mechanical and functional potentials as well as abundant element‐constitutions of designing, surface coatings composed of HEA‐based materials are considered to have promising applications in engineering and industrial manufacturing. Abstract : High entropy alloy (HEA) coatings can effectively enhance mechanical and functional properties of the substrate components. This review summarizes the fabrication and post‐treatment processes, the functional properties, and the underlying mechanisms of the HEA‐based coatings. Moreover, the future development tendency and challenges of the HEA‐based coatings regarding the scientific research and industrial applications are prospected.